In Vitro Determination of SunProtective Factor (SPF) of Dadap Serep (Erythrina Subumbrans (Haks.) Merr.) Leaf Extract Using Spectrophotometric Method - Maharini, Indri (Journal of Chemical Natural Resources, 2019)
Dadap serep (Erythrina Subumbrans Haks Merr) contains bioactive compounds of flavonoids, saponins, isoflavones, alkaloids, and lectins. Flavonoid compounds have a sunscreen effect. This studyaimed to determinethe value of Sun Protective Factor (SPF) using spectrophotometry method with variations in the extract concentrations, such as500 ppm,750 ppm, and 1000 ppm.The results showed that the SPF values of each concentration were11.47 ±0.583335, 17.05 ± 0.898838,21.93 ± 0.791557, respectively. In conclusion, the ethanol extract of dadap serep hastheability to become sunscreen in the maximal and ultra category.